EVALUATION OF ERODIBILITY INDICES AND SOIL PROPERTIES AS AFFECTED BY LAND-USE TYPES IN MBANO SOUTH-EAST NIGERIA - OSUJIEKE, DONALD NWEZE (Journal of Agricultural Sciences (Belgrade), 2020)
Abstract: Soil erosion has been at the forefront in degradation of soils under different land-use types in southeast Nigeria. Hence, this research was aimed at determining the erodibility of the soils under different land-use types in Mbano. The four land-use types selected were oil palm plantation (OP), cassava farm (CF), pineapple orchard (PO) and plantain plantation (PP). However, clay dispersion ratio (CDR), clay dispersion index (CDI) and clay flocculation index (CFI) was they erodibility indices used.  A total of 5 composite samples were collected randomly from each of the land uses at a depth of 0 – 20 cm using free survey. They samples were subjected to laboratory analysis. Data generated were analyzed statistically using completely randomized design of analyses of variance (ANOVA) and correlation. CDR had an increasing order of 47.92 %